Characterization of High‐m ULF Wave Signatures in GPS TEC Data. Issue 14 (23rd July 2021) - Zhai, Changzhi; Shi, Xueling; Wang, Wenbin; Hartinger, Michael D.; Yao, Yibin; Peng, Wenjie; Lin, Dong; Ruohoniemi, J. Michael; Baker, Joseph B. H.
Abstract: GPS total electron content (TEC) measurements were used to investigate high‐m ultralow frequency (ULF) waves during the recovery phase of a geomagnetic storm. ULF wave signals in TEC data show high coherence and significant common power in the wavelet coherence and cross wavelet transform analyses with magnetic field radial component data from GOES‐15. They did not cause significant ionospheric scintillation or ground magnetic signatures due to ionospheric screening effects. An automatic identification procedure is developed to identify ULF wave signature in TEC data from 10 GPS receivers on January 25, 2016. The waves were mainly distributed on the dayside and post dusk sector from ∼64° to ∼71° magnetic latitude. This is the first time that the large‐scale 2D spatial structure and temporal evolution of high‐m ULF waves are revealed, which demonstrates TEC measurements as an effective high‐m ULF wave remote sensing tool. Plain Language Summary: Ultralow frequency (ULF) waves with periods from 1 s to more than 10 min can interact with particles in the magnetosphere and affect the ionospheric electric field as well as the geomagnetic field. Determining how ULF waves propagate from the magnetosphere to the ionosphere, and ground, and how the wave power is distributed spatially and evolves over time is important for understanding the role of ULF waves in magnetosphere‐ionosphere coupling. ULF waves with large azimuthal wave numbers (high‐m) are usually screened from the ground by the ionosphere and thus not detected by magnetometers. Due to the limitations in spatial coverage of satellites and ground radar observations, it has been difficult to examine the large‐scale spatial structure and temporal evolution of high‐m ULF waves during a single event. In this study, we used data from multiple instruments to analyze the characteristics of the high‐m ULF waves that occurred during January 24–26, 2016. The ULF wave signatures in GPS total electron content (TEC) showed similar time evolution and frequency variations to GOES satellite measurements. By using abundant GPS TEC data and automatic identification procedure, the large‐scale 2D spatial structure and time evolution of high‐m ULF waves are disclosed for the first time. Key Points: 2D spatial structures and time evolution of high‐m ultralow frequency (ULF) waves are revealed for the first time using total electron content (TEC) data ULF waves in TEC data show high coherence, similar temporal distribution and frequency evolution with wave signatures in GOES B r data The high‐m waves caused neither ionospheric scintillations nor ground magnetic signatures